SIKAP PESERTA DIDIK SMP TERHADAP SIKAP SAINS DI KABUPATEN SUMBAWA BARAT - Hamdani,; Eka Prihatin, (Journal of Innovation Research and Knowledge, 2021)
The purpose of this study was to analyze the application of Learning Cycle 5E (LC 5E) to the attitudes of students in Science. The initial stage in this study was to develop learning devices that referred to the Four-D (4D) model. Learning tools in the form of Syllabus, Lesson plan, Inquiry Worksheet, and research instruments in the form of questionnaires attitude towards students of science. The research was carried out on junior high school students in West Sumbawa Regency, with a sample of 290 students. The research design used was the Control group pre-test post-test. Data was collected by an attitude questionnaire adopted from TOSRA (Indonesian translation). The research data calculated the normalized gain (N-gain) and analyzed with the help of SPSS version 16 for windows. The results showed that the N-gain class that applied the LC 5E obtained a value of 0.41 with a medium category higher than the class that did not apply the LC 5E which obtained a value of 0.39 with a medium criteria. The results of the research analysis showed a pre-test with a value of p (Sig.) 0.287> 0.05, so there was no difference between the classes applied in the LC 5E and those not implemented in the 5E model, and the post-test results obtained p (Sig.) 0 , 00 <0.05 then, indicating there is a difference between the classes applied in the LC 5E and those that are not applied in the LC 5E. Thus it can be assumed that the application of the LC 5E in schools can improve the attitude of students towards science.